PENGARUH KOMPENTENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. MEDIA NUSANTARA CITRA TBK - Hery Wihasnanto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This research is aims to determine the effect of competency and compensation on employee performance, the effect of compensation on employee performance taking this sample using the simple random sampling method. The data is then analyzed using regression, based on data analysis, it is known that the competency and compensation variables have a significant effect on employee performance. This means that competence and compensation affect employee performance simultaneously. Partially competency variables affect significant employee performance. This means that the competency variables have a significant effect on employee performance. The compensation variable partially affects significant employee performance.